2021
DOI: 10.1002/sctm.21-0046
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Mesenchymal Stromal Cells as Critical COVID-19 Adjuvant Therapy: A Randomized Controlled Trial

Abstract: One of the main causes of acute respiratory distress syndrome in coronavirus disease 2019 (COVID-19) is cytokine storm, although the exact cause is still unknown. Umbilical cord mesenchymal stromal cells (UC-MSCs) influence proinflammatory T-helper 2 (Th 2 ) cells to shift to an anti-inflammatory agent. To investigate efficacy of UC-MSC administration as adjuvant therapy in critically ill patients with COVID-19, we conducted a double-blind, multicentered, randomized controlled trial at four COVID-19 referral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
206
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(217 citation statements)
references
References 35 publications
6
206
4
1
Order By: Relevance
“…After screening 52350 titles and abstracts and 1029 full texts, 47 unique randomised controlled trials that evaluated antiviral antibody or cellular treatments were identified as of 21 July 2021 (fig 1). 43444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788 A table of excluded full texts is provided in the supplementary data on bmj.com. Searches of living evidence retrieval services identified 11 publications of eligible randomised trials, which were reconciled with our formal search strategy when necessary 222324254549566466676875838688.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening 52350 titles and abstracts and 1029 full texts, 47 unique randomised controlled trials that evaluated antiviral antibody or cellular treatments were identified as of 21 July 2021 (fig 1). 43444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788 A table of excluded full texts is provided in the supplementary data on bmj.com. Searches of living evidence retrieval services identified 11 publications of eligible randomised trials, which were reconciled with our formal search strategy when necessary 222324254549566466676875838688.…”
Section: Resultsmentioning
confidence: 99%
“…One randomised trial was identified after the data analysis: Dilogo 202153 (registration No NCT04457609), a trial of umbilical cord mesenchymal stromal cells versus placebo in 40 participants. It will be included in the next update.…”
Section: Resultsmentioning
confidence: 99%
“…Phase I and II clinical studies have shown that MSCs transplantation is a safe and potentially effective method for the treatment of moderate to severe ARDS [63,64]. Besides, recent exploratory clinical studies showed that MSCs treatment was associated with improvements in mortality, dyspnea and chest imaging findings for severe and critically ill COVID-19 patients [65][66][67][68][69]. And phase I and II clinical trials have also shown that intravenous MSCs infusion in patients with moderate and severe COVID-19 is safe and well tolerated [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…In some case reports, the UC- MSC transplantation also improved lung inflammation based on lung CT images 32,34,35, 38 . The laboratory tests showed that almost all patients treated with UC-MSC transplantation had decreased CRP, IL-6, and TNF-α 5,26-28, 31 , and this reduction could be detected early in days 2 -3 post-transplantation [31,40] or later at 7 -14 days post-transplantation 26,28 . However, Wei et al (2021) showed that although there were significant improvements in symptoms, the biomarkers of CRP, IL-6, and TNF-α were not significantly reduced after 1 -3, 5 -8, and 12 -16 days following UC-MSC infusion 24 in a study of 12 patients.…”
Section: Publications On Uc-msc Transplantation For Covid-19 Patientsmentioning
confidence: 97%